PENGARUH PERBANDINGAN PASTA KECAMBAH KACANG TUNGGAK (Vigna unguiculata L.) DAN PASTA RUMPUT LAUT (Eucheuma cottonii) TERHADAP KARAKTERISTIK SOSIS ANALOG KACANG TUNGGAK - Wiantini, Kadek; Ekawati, I Gusti Ayu; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 2 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i02.p05, 2019)
This study aims to determine the effect of cowpea sprout paste and seaweed paste to the characteristics of analogue cowpea sausage, and to know the right ratio of cowpea sprout paste and seaweed paste on the characteristics of analogue cowpea sausage. The experimental design used was completely randomized design with the treatment ratio of cowpea sprout paste and seaweed paste, which consists of 5 levels such as: 90% cowpea sprout paste : 10% seaweed paste, 80% cowpea sprout paste : 20% seaweed paste, 70% cowpea sprout paste : 30% seaweed paste, 60% cowpea sprout paste : 40% seaweed paste, and 50% cowpea sprout paste: 50% seaweed paste. The treatment was repeated 3 times to obtain 15 units of experiments. The data were analyzed by variance analysis and if the treatment had a significant effect then continued with DMRT (Duncan Multiple Range Test). The results showed that cowpea sprout paste and seaweed paste ratio had a significant effect on water content, protein content, fat content, carbohydrate content, coarse fiber content, elasticity, taste (hedonic), texture (hedonic and scoring) and overall acceptance (hedonic). Comparison of 50% cowpea sprout paste and 50% seaweed paste had the best characteristics analogue cowpea sausage, with 69,88% water content, 2,16% ash content, 3,77% protein content, 2,92% fat content, 21,27% carbohydrate content, 1,50% coarse fiber content, elasticity 6,65 N, color and aroma rather liked, texture chewy and liked, taste and overall acceptance liked.